2019
DOI: 10.14710/jitaa.44.4.335-345
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of D-loop mitochondrial DNA (mtDNA) sequence in Bali and Sumba Ongole cattle breeds

Abstract: This study aimed to investigate the diversity of the complete sequence of D-loop mitochondrial DNA (mtDNA) in Bali and Sumba Ongole (SO) cattlebreeds. A total of 24 blood samples were collected from Bali cattle (19 heads) and SO cattle (5 heads), and were extracted and then analyzed to obtain the sequence of D-loop mt DNA.Multiple alignments of the whole sequence of D-loop mtDNA were determined using clustal W. Genetic distance was calculated using a p-distance method, while the genetic tree was constructed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The nucleotide composition of A-T was higher than G-C. This result was conducted well with the previous study in Bali cattle, including d-loop sequenced [6,7], Cyt-b sequenced [8,9], COI [10]. This finding is also consistent in another breed of cattle.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The nucleotide composition of A-T was higher than G-C. This result was conducted well with the previous study in Bali cattle, including d-loop sequenced [6,7], Cyt-b sequenced [8,9], COI [10]. This finding is also consistent in another breed of cattle.…”
Section: Resultssupporting
confidence: 90%
“…No reports about 16S rRNA sequenced in Bali cattle. Most phylogenetic studies in Bali cattle using d-loop [6,7], Cyt-b sequenced [8,9], COI [10,11]. Thus, the objective of this research was to identified a phylogenetic tree among Bali cattle and four cattle breeds (Bos indicus, Bos taurus, Bos frontalis, and Bos grunniens) based on partial sequenced of 16S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough understanding of livestock diversity and population structure is required for maintaining genetic variation and is crucial for developing future breeding strategies, and the use of molecular technology for this purpose is gaining popularity [ 7 ]. Previously, the genetic diversity of SO cattle has been investigated through various analyses utilizing low-density microsatellite markers and mitochondrial DNA markers [ 8 , 9 ]. The revolution in molecular approach and the increasing availability of a large number genome-wide single nucleotide polymorphisms (SNPs) of animals have transformed them into the most important markers, and they are now intended to be used for genetic studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternally inherited mitochondrial DNA (mtDNA) has been extensively used to determine the genetic variation and phylogenetic relationships of domestic cattle, but related studies have been mostly restricted to the short hypervariable region which makes it impossible to clearly distinguish between some important ancient branches within the phylogenetic tree. To date, most mtDNA studies have focused on the control region (D-loop) (Jakaria et al 2019). Therefore, the present study aims in including the additional information on the matrilineal genetic diversity and phylogenetic status of the cattle breeds of Tamil Nadu using mitochondrial DNA (mtDNA) sequence data obtained from the whole genome sequencing.…”
Section: Introductionmentioning
confidence: 99%